Teachers ’ Perceived School Level Sources of Low Retention in Remote Secondary Schools in Tanzania - Boniface, Raymond M. (Papers in Education and Development, 2020)
Retaining quality teachers especially for schools located in remote poor contexts remains a problem of critical focus in different parts of the world. Strategies to retain teachers in many Sub-Saharan countries such as Tanzania, for example, have been ' hardly achievable ' because of being monetary-based when such a resource is usually scarce and unsustainable in most of these countries. Extant literature identifies organisation-based strategies for retaining teachers as a more promising area for consideration in situations where financially related strategies cannot be sustained. This paper, therefore, discusses the teachers ' perceived school level sources of low retention in secondary schools based in remote areas. The paper reports the findings of a study that was conducted in three districts of Kondoa, Mpwapwa and Chemba, Dodoma region, central Tanzania. It was guided by the Organisational support theory and adopted mixed methods approach claiming pragmatic knowledge. Data were collected in three phases, that is, the pilot, survey (using a questionnaire) and follow-up interviews. A sample included 28 schools, 27 school heads and 231 teachers. Qualitative data from interviews and open-ended items from questionnaires were subjected to Content Analysis whereas data generated from close-ended items in the questionnaires were analysed with the help of the IBM Statistical Package and Service Solutions (SPSS). Findings show that teachers perceive five key school level sources of low retention in remote schools: Accommodation and social services, school level conflicts, poor teaching and learning conditions, teachers ' involvement in decision-making, and lack of alternative economic activities. Arguably, these are more viable issues for consideration as 66 most of them could be dealt with using school level resources.